COVID-19, aftermath, impacts, and hospitality firms: An international perspective. (October 2020) - Duarte Alonso, Abel; Kok, Seng Kiat; Bressan, Alessandro; O'Shea, Michelle; Sakellarios, Nikolaos; Koresis, Alex; Buitrago Solis, Maria Alejandra; Santoni, Leonardo J.
Highlights: Examines impacts, coping strategies, and adjustments in light of COVID-19. Selects an international sample of hospitality operations. Considers insights of the resilience literature and theory. Develops theoretical frameworks emerging from the chosen inductive approach. Proposes theoretical and practical implications can illuminate future research. Abstract: Drawing on the theory of resilience, and on an international sample of 45 predominantly small hospitality businesses, this exploratory study extends knowledge about the key concerns, ways of coping, and the changes and adjustments undertaken by these firms' owners and managers during the COVID-19 outbreak. The various emergent relationships between the findings and the considered conceptual underpinnings of the literature on resilience, revealed nine theoretical dimensions. These dimensions critically illuminate and extend understanding concerning the actions and alternatives owners-managers resorted to when confronted with an extreme context. For instance, with financial impacts and uncertainty being predominant issues among participants, over one-third indicated actioning alternative measures to create much-needed revenue streams, and preparing for a new post-COVID-19 operational regime, respectively. Furthermore, 60 percent recognised making changes to the day-to-day running of the business to respond to initial impacts, or biding time in anticipation of a changing business and legal environment.